User satisfaction regarding the libraries facilities in Perpustakaan Tun Dr. Ismail (PTDI), UiTM Cawangan Johor Bahru, Kampus Pasir Gudang / Nurul Aizzat Mohd Saidi - Mohd Saidi, Nurul Aizzat (UiTM Cawangan Johor Kampus Pasir Gudang, 2014)
This study aims to focus on the level of satisfaction of students regarding the facilities accommodation provided in Library of' UiTM Johor Bahru, Kampus Pasir Gudang. Showing also the requirement and recommendation of facilities in the libraries. Design/methodology/approach - 322 of questionnaire developed and being distributed. It were to evaluate the satisfaction of users about the library facilities and gather information from the students. A survey on terms of agreed and disagreed which needed to be scaled from one to five points. Question were regarding their satisfaction, recommendation and also problem that they always faced in library. Finding : Results shows majority of students were satisfied with the library facilities. From these research a solution and problems has been ident(fled to improve the performance of library in the future.